2006
DOI: 10.1111/j.1440-1819.2006.01504.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of completed and attempted suicide in Akita, Japan

Abstract: To determine the factors underlying suicide in Akita prefecture, a questionnaire survey was conducted among members of the Akita Prefectural Medical Association (APMA), regarding suicide cases they attended. During the investigation period (1 July 2001-30 June 2002), the total number of suicide cases was 243 (138 completed, 105 attempted). Significant differences were identified between completed and attempted suicide groups in terms of gender, age distribution, and suicidal methods. Specifically, in the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 33 publications
5
75
2
Order By: Relevance
“…The question of 2 populations of suicidal people is old, based mostly on epidemiologic data [38,39]. In a more recent study, Fushimi et al [40] compared completed with attempted suicide, and found more frequent younger subjects and subjects with a history of suicide attempts in the second group.…”
Section: Discussionmentioning
confidence: 99%
“…The question of 2 populations of suicidal people is old, based mostly on epidemiologic data [38,39]. In a more recent study, Fushimi et al [40] compared completed with attempted suicide, and found more frequent younger subjects and subjects with a history of suicide attempts in the second group.…”
Section: Discussionmentioning
confidence: 99%
“…The demographics remain stable with suicides completed at the highest rate by White older males, and suicide attempts by teens, young adults, women, and African Americans (Spicer & Miller, 2000). Other studied risk factors besides previous suicide attempts include maladaptive personality traits such as impulsivity and aggression (Brezo et al, 2007;Wyder & DeLeo, 2007); psychiatric diagnoses such as bi-polar disorder and schizophrenia (Fushimi et al, 2006;Hamlin, 2004;Keilp et al, 2006); psychological factors such as depression, hopelessness, social problem-solving deficits, and cognitive distortions (Pollock & Williams, 2004;Yufit & Lester, 2005); experiential trauma such as child physical or sexual abuse (Brezo et al, 2007), and drug abuse/dependence (Brezo et al, 2007;Hamlin, 2004). Sher and colleagues (2007) concluded that depressed suicide attempters with comorbid alcohol-use disorders had higher aggression and impulsivity levels; so they often had higher rates of lethality compared to other groups without alcohol-use disorders.…”
Section: Literature Reviewmentioning
confidence: 98%
“…While theories surrounding a subject's motivation to die have evolved, the capability to measure plausible intent remains out-ofreach, requiring researchers to identify risk factors and their relationships to suicide (Brezo et al, 2007;Brown et al, 2005;Forman, Berk, Henreques, Brown & Beck, 2004;Fushimi et al, 2006;Jollant et al, 2005;Keilp et al, 2006;Wyder & DeLeo, 2007;Zalsman et al, 2006;Zhang & Lester, 2008). The field of suicidology focuses on the identification of risks that strengthen and intervention/prevention strategies that weaken the association between strain and suicide ideation and attempts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…When the individual involves the police, then a larger circle of highly emotional people are involved reviewing, judging, condemning, and redressing. Mental illness and consequently the treatment of mental illness are often included in the formula of suicide and suicide prevention (Fushimi, Sugawara, & Saito, 2006;Hamlin, 2004;Keilp et al, 2006;Lord, 2000;Yufit & Lester, 2005). The police are the front-line responders for mental health emergencies (Steadman, Morrisey, Deane, & Borum, 1999), including suicide attempts.…”
Section: Introductionmentioning
confidence: 99%